Original paper Thiopurine S-methyltransferase gene polymorphism in pemphigus vulgaris - Genc, Ahmet; Gunasti, Suhan; Tuli, Abdullah; Curuk, M. Akif; Uzun, Soner (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : Thiopurine S-methyltransferase (TPMT) genotypes or phenotypes are important as a predictive factor for thiopurine-induced toxicity. Individuals who are TPMT deficient or have intermediate TPMT activity are at risk of developing myelosuppression and life-threatening leucopenia when treated with standard doses of thiopurines; thus, pretreatment identification of these individuals is very important. Aim: The aim of this study was to analyze the TPMT gene polymorphisms in pemphigus vulgaris patients who were treated with azathioprine. Material and methods : Fifty-four patients with pemphigus vulgaris were analyzed and treated with azathioprine. The TPMT genotyping of these patients was carried out by an allele-specific PCR, PCR-restriction fragment length polymorphism (RFLP) assay and DNA sequencing. Results : The distribution of TPMT genotypes was 96.7% as wild-type TPMT*1/TPMT*1, 1.85% as heterozygous TPMT*1/TPMT*3A, and 1.85% as heterozygous TPMT*1/TPMT*2. Fifty-two samples without carrier mutant alleles, described as TPMT*1, had no toxicity when treated with a standard dosage of azathioprine. However, the patient who was characterized as heterozygous TPMT*3A developed severe myelosuppression after the standard doses of azathioprine. The second patient characterized as heterozygous TPMT*2 was then treated with methylprednisolone without any adverse effects. Conclusions : These data indicate that TPMT gene polymorphism detection might be important in pemphigus vulgaris before the patients are treated with azathioprine.